Activity theory analysis of the virtualisation of teaching and teaching environment in a developing country university - Adam, I.O.; Effah, J.; Boateng, R. (Education and Information Technologies, 2019)
This study aims to understand how a developing country higher education institution (HEI) attempted to digitalise teaching. The Internet has disrupted the traditional teaching environment and teaching practices leading to the migration from physical face-to-face teaching to online teaching changing the work environment of the teacher. Information systems literature has examined the academic environment of HEIs from student’s perspective in a virtual learning environment but not from the instructor’s perspective in a teaching work environment. How the teaching work environment can be virtualised has not also been widely explored. Using activity theory and an interpretive case study approach data was obtained from interviews, documents and participant observation. Using hermeneutics as the mode of analysis the findings reveal how tools: an open source technology and rules are modified through the resolution of contradictions to suit developing country context of the HEI. The study provides practitioners insights on how emerging contradictions in tools, implementers and rules in a teaching work environment virtualisation can be used as an avenue for development. It also offers insight into how HEIs can migrate their physical teaching environment to online.
Keywords: Virtual teaching; Work environment; Virtualisation; Activity theory; Higher education institution; Developing country